Film and Communication Desire: Visual Semiotics and Psychological Persuasion in Documentary Netflix's 'Flavorful Origins' as Gastronomic Representation - Setyawan Prabowo, Henricus Hans (Airlangga University, 2025)
This paper investigated how Netflix’s culinary docuseries Flavorful Origins constructs culinary authenticity via visual continuity and psychological communication mechanisms. Through analyzing three emblematic episodes (“Mutton,” “Noodles,” and “Potato”), relationships between cinematography, narrative sequencing, and cultural representation were examined. By utilizing Bordwell and Thompson’s continuity framework, Barthesian visual semiotics, and communication theory, this paper identified three mechanisms—geographic anchoring, sensory choreography, and temporal scripting—that together played out the authenticity of the episode. The paper argues that as 78% of the frames are close-ups of materiality, viewers’ visual syntax fetishizes materiality while activating sensory priming and embodied cognition. A paradox emerges between the series’ traditional and material authenticity claims and conformance to commercial food-media aesthetics with hyper-color grading. The paper argues that Flavorful Origins commodifies authenticity through “culinary nationalism,” using continuity editing to package regional Chinese cuisines as ethnographically truthful but globally desirable. Psychological communication mechanisms such as parasocial engagement and desire cultivation work through visual rhetoric to activate embodied responses that go beyond cultural documentation, showcasing food media as psychological persuasion and identity negotiation. These findings contribute to critical food media studies through revealing how streaming platforms remediate cultural authenticity through standardized visual regimes in the era of digital gastronomy. Keywords: Desire; Culinary Authenticity; Visual Semiotics; Netflix Docuseries